The tendering process for "cadangan pembangunan 2986 Unit Pangsapuri di Jalan Taman Metro Perdana Barat, Taman Metropolitan, Kepong, Mukim Batu, Daerah Kuala Lumpur, Wilayah Persekutuan" - Shaifol Bahari, Natasha Aziera (Universiti Teknologi MARA, Perak, 2019)
A submission of tender were made by a prospective supplier in response to invitation of tender. It makes an offer for the supply of goods or services. An invitation to tender might be issued for a range of contracts, including equipment supply, the main construction contract, etc. Therefore, this report will be discussing about all matters related to tendering. This case study is made based on construction site of Residensi Kepongmas Kuala Lumpur under the company named Kenwingston Sdn. Bhd. The main objectives of this report is to discuss on the process of tender from the early stage which is "Pre-Tender Review" until the final stage called "Tender Result".